4-Aryl-N-phenylpyrimidin-2-amines targeting EGFR-tyrosine kinase attenuated EGFR-expressing cell lines - Lueacha Tabtimmai; Prapasri Supakun; Borvornvat Toviwek; Nattanan Jiwacharoenchai; Duangnapa Kiriwan; Thitinan Aiebchun; M. Paul Gleeson; Kiattawee Choowongkomon (Elsevier, 2022)
Target therapies have been widely developed to combat various diseases and cancer. Epidermal Growth Factor Receptor is still a currently therapeutic target for solid tumor. Aberration of EGFR activity or expression reflect disease progression and poor prognosis. Recently, several newly synthesized 4-aryl-N-phenylpyrimidin-2-amines with some modifications at R2 selectively elicited cytotoxicity against A549. Therefore, harboring EGFR expression would be reasonable for the assessment. Herein, the 4-aryl-N-phenylpyrimidin-2-amines derivatives; N-(3-{[4-(4-methoxyphenyl) pyrimidin-2-yl]amino}phenyl), 3-{[4-(3-methoxyphenyl) pyrimidin-2-yl] amino}benzene-1-sulfonamide.(13g), methanesulfonamide (13c), 3-[(4-phenylpyrimidin-2-yl)amino] benzene-1-sulfonamide (13f) and 3-(benzene-1-sulfonamide) (5) were selected as promising derivatives for targeted-EGFR analysis. Kinase enzymatic-based assay exhibited IC50 values of 5.61, 31.92, 73.80 and 0.79 ​nM of each derivative, respectively whilst 41.50 ​nM of Gefitinib. Molecular docking deciphered the mode of binding of each derivative in ATP-binding site greater than gefitinib. Although, (13g) demonstrated the highest binding free energy among the other but not in ATP-binding site as the others does that related to its IC50 values. (13c), (13f), and (5) therefore were subjected for cell-based analysis. A549 and A431 were used as wtEGFR-expressing cells for cell-based assay. (13c), (13f), and (5) had high toxicity towards in both cells while (5) had much more toxicity on A431. (13c), (13f) and (5) not only induced apoptosis in a dose-dependent manner but reduced clonogenic formation greater than gefitinib. Migration of EGF-stimulated A431 was significantly delayed by the compounds over time but they could not delay EGF-stimulated A549 migration. Taken together, (13c), (13f) and (5) would be a newly synthesized derivative by targeting wtEGFR-expressing cells that attenuated EGFR-driven cancer hallmark leading to targeted therapy development.